The Effect of Drill Training on Underhand Passing Ability in High School Students - Uly, Arfin; Hudain, Muh. Adnan; Adil, Ahmad; Kamaruddin, Ilham; Fahrizal, Fahrizal (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study aims to determine the effect of drill training on students' underhand passing ability in high school. The method used was an experiment with a pretest-posttest design, involving 18 students divided into two groups at SMAS Datok Sulaiman Palopo. The first group underwent drill passing training against the wall, while the second group underwent pair passing instruction. Data were collected through underhanded passing ability tests before and after training. The results showed that there was a significant effect of drill training on underhanded passing ability. In the wall training group, the average score increased from 9.11 (pretest) to 11.89 (posttest), with a difference in the increase of 2.78 points and a significance value of 0.000 (p < 0.05). In the pair training group, the average score increased from 9.33 (pretest) to 12.22 (posttest), with a difference in increase of 2.89 points and a significance value of 0.001 (p < 0.05). The decrease in standard deviation in the pair group from 2.236 to 1.333 indicated an increase in consistency. The conclusion of this study is that both training methods proved effective in improving underhand passing ability, with paired training showing slightly higher improvements than wall training. This study contributes to the development of school training programs to improve students' sports skills.